Pengaruh Keputusan Investasi, Keputusan Pendanaan, Kebijakan Dividen, Good Corporate Governance Dan Corporate Social Responsibility Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Go Public Yang Terdaftar Di Corporate Governance Perception Index (CGPI) Periode 2009-2013) - Darussalam, Wildan Aji (2016)
This study aims to test empirically the impact of investment decisions, financing decisions, dividend policy, good corporate governance and corporate social responsibility on firm value. The objects of study are all of go public companies listed in Corporate Governance Perception Index (CGPI) during 2009-2013. Population of this study is the go public companies listed in Corporate Governance Perception Index (CGPI) during 2009-2013. The study used purposive sampling method to collect the sample. Based on certain criteria, there were 53 go public companies that matched with the sample, but from the sample have 3 companies with outlier data. Because the outlier of data, the sample from this study are 50 companies. The analysis of statistic on this study used multiple regression analysis. The result of this study showed that investment decision (PER) has the significant effect on firm value, financing decision (DER) has not the significant effect on firm value, dividend policy (DPR) has the significant effect on firm value, good corporate governance (GCG) and corporate social responsibility (CSR) does not have the significant effect on firm value.